Challeng in Pronouns Translation: An Analysis of 'Noktah Merah Perkawinan' Subtitles - Hasana, Nurul; Prihantoro, Prihantoro (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
In Indonesian, intimacy, social status, and politeness can be linguistically marked. Conversely, a near equivalent English pronoun cannot always completely contextualize the foregoing aspects. This study examines the translation of pronouns in movie subtitles entitled “Noktah Merah Perkawinan” to see if aspects beyond meaning, such as politeness and hierarchy, are conveyed. Data for this study were collected from subtitles in both Indonesian and English. A parallel corpus and mark segment were created for each pronoun found in both subtitles, and pronouns were identified bidirectionally. Using Molina & Albir's translation techniques and Sneddon's analytical schemes of Indonesian pronouns, the translations were analyzed in relation to theories of politeness and grammar. The findings reveal that some translations are acceptable and semantically accurate, but some fail to convey social aspects, kinship relationships, and levels of politeness as expressed in the source language (Indonesian). We argue that this is caused by cultural and grammatical differences between Indonesian and English. These findings have significant social implications, highlighting the need for deeper cultural understanding  in translation practices. When the translated pronouns fail to convey crucial social dynamics, such as hierarchy or respect the subtitled content may unintentionally misrepresent interpersonal relationships, impacting cross-cultural communication.